ECOTIRE: A New Concept of a Smart and Sustainable Tire Based on a Removable Tread - Daniel Garcia-Pozuelo; Farshad Afshari; Ramon Gutierrez-Moizant; Miguel A. Martínez (Applied Sciences)
This paper introduces a new concept of a smart and sustainable tire based on a removable tread band: ECOTIRE. Current tires, though crucial for road information and vehicle control, such as braking, traction, and turning, remain disconnected from Advanced Driver Assistance Systems (ADAS). Additionally, their production, use, and recycling pose significant environmental challenges, requiring sustainable materials and lifecycle improvements. The ECOTIRE concept makes it possible to separate the part of the tire subject to wear and apply new materials with reduced environmental impact. At the same time, the service life of the casing is extended, facilitating the introduction of sensors that improve vehicle safety. This study explores the purely mechanical connection between the casing and tread, demonstrating the feasibility of this innovative tire structure while eliminating the need for rubber matrix-based materials for a proper bond between the two components. Experimental tests using a rubber sample to simulate the tire–road contact patch validate the effectiveness of the mechanical link under varying normal loads. Grip test results, measuring longitudinal and lateral forces, show promising performance. This advancement in tire technology marks a first step toward sustainability, tire performance, and smart integration, ultimately reducing environmental impact.